Gustave Roussy Immune Score as a Novel Prognostic Scoring System for Colorectal Cancer Patients: A Propensity Score Matching Analysis - Tian, Shan; Cao, Yinghao; Duan, Yanran; Liu, Qi; Peng, Pailan (Frontiers in Oncology, 2021)
Aim: The Gustave Roussy Immune Score (GRIm-Score) was originally designed to select cancer patients for immunotherapy, and later reported to be a novel prognostic scoring system in lung cancer and esophageal cancer. This study was aimed to determine the prognostic role and predictive performance of GRIm-Score in CRC patients. Methods: We conducted a single-institution study of 1579 adult CRC patients receiving surgical removal, and those patients were divided into low GRIm-Score group (score 0,1) and high GRIm-Score group (score 2,3). Propensity score matching (PSM) was excuted to balance the potential confounding factors between the two groups. Survival and time-dependent receiver operating characteristic (Td-ROC) analyses were applied to depict the prognostic role and predictive significance of GRIm-Score in CRC patients. Results: There were 200 cases CRC patients in high GRIm-Score group and 1379 cases in low GRIm-Score group. CRC patients with high GRIm-Score exhibited higher proportion of advanced TNM stage, large tumor size, postoperative chemotherapy, and high levels of serum CEA, CA125, NLR, PLR, SII, PNI, ALRI. Survival analysis revealed that CRC patients in high GRIm-Score group showed worse overall survival (OS, P<0.0001) and disease-free survival (DFS, P<0.0001) compared with those in low GRIm-Score group. Results from multivariate Cox regression implicated that high GRIm-Score was not only a potent prognostic index for unfavorable OS (HR=1.622, 95%CI: 1.118-2.355, P=0.0109), but also a potent risk factor for worse DFS (HR=1.743, 95%CI:1.188-2.558, P=0.0045). Td-ROC analysis demonstrated that GRIm-Score exhibited the superior discriminatory power in the prediction of OS and DFS when compared to SII, PNI and ALRI. Such strong associations between high levels of preoperative GRIm-Score and unfavorable survival outcomes remained robust after PSM analysis. Conclusion: GRIm-Score, a novel inflammatory and nutritional risk scoring system, is a potent prognostic index in CRC patients receiving surgical removal. GRIm-Score can be used as an effective and simplified risk stratification tool for postoperative survival prediction of CRC patients.